Influence of different training activities on development of junior athletes' logical thinking - Khoroshukha, M.; Griban, G.; Terentieva, N.; Tkachenko, P.; Petrachkov, O.; Semeniv, B.; Otravenko, O.; Dikhtiarenko, Z.; Yeromenko, E.; Khurtenko, O.; Lytvynenko, A. (International Journal of Human Movement and Sports Sciences, 2021)
The aim of this study is to investigate the influence of different training activities on the development of the logical thinking of junior athletes who specialize in various sports. 131 students-athletes and 77 students-non-athletes aged 17-20 took part in the study. They were divided into two experimental groups (group A and group B) and one control group (group C). Group A included 69 students-athletes who were engaged in speed and power sports (boxing, freestyle wrestling, sprinting, hurdling, jumping, throwing). Group B included 62 students-athletes who were engaged in endurance sports (skiing, cycling, swimming). Group C included 77 students of higher education institutions who did not do sports. The study of the athletes' logical thinking was carried out according to the methodology of "Numerical series". It was found that the student-athletes who were engaged in endurance sports (group B) were registered to have significantly better (p<0.05-0.001) values of all three indicators of logical thinking (number of errors, speed of thinking and general assessment of the state of logical thinking) in comparison with the student-athletes who were engaged in speed and power sports (group A) andstudents-non-athletes (group C). Moreover, it was established that the students-non-athletes had a significant improvement in the indicators of logical thinking in comparison with the students-athletes who were engagedin speed and power sports (p<0.05-0.001).